PEMANFAATAN TEKNOLOGI DALAM UPAYA MERUBAH PERILAKU PELAKU USAHA HOME INDUSTRI DALAM MEMASARKAN DAN MENJUAL PRODUK - Darlan Darlan; Rahma Novianti (Journal of Empowerment and Community Service (JECSR), 2022)
In this service, we will introduce and provide insight into the influence of technology on home industry business actors in marketing and selling their products. This service is carried out using the location survey method, interviews, and then an introductory stage of socialization regarding the use of technology to market and sell products online. Technological developments attract business actors to increase their knowledge and learn more deeply to market and sell their products even better. After the implementation of this service, it is hoped that home industry business actors in the East Sempaja Village can utilize technology by using online businesses such as marketing and sales on social networks such as Facebook and Instagram using email or websites so as to increase income from these products.